2017
DOI: 10.1007/s00038-017-1049-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of non-physical peer sexual harassment on high school students’ psychological well-being in Norway: consistent and stable findings across studies

Abstract: Objectives The paper examines how strongly non-physical peer sexual harassment is associated with a wide range of well-being outcomes from symptoms of depression and anxiety to self-esteem and body image. Methods Two large community samples of high school students were analyzed (n = 1384 and n = 1485). Students responded to questionnaires on being subject to nonphysical sexual harassment, sexual coercion and forced intercourse, and to well-being indicators ranging from anxiety, depression, self-esteem, body im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 29 publications
10
60
0
17
Order By: Relevance
“…Results from this study confirm results from previous studies that show girls to be more frequently victimized by sexual harassment [3][4][5][6]24]. A nation-wide survey in Sweden shows that this pattern lingers in adulthood, with more women than men reporting sexual harassment [25].…”
Section: Prevalence Of Online and Offline Sexual Harassmentsupporting
confidence: 88%
See 2 more Smart Citations
“…Results from this study confirm results from previous studies that show girls to be more frequently victimized by sexual harassment [3][4][5][6]24]. A nation-wide survey in Sweden shows that this pattern lingers in adulthood, with more women than men reporting sexual harassment [25].…”
Section: Prevalence Of Online and Offline Sexual Harassmentsupporting
confidence: 88%
“…In a countrywide Finnish study, 55% of girls and 40% of boys reported sexual victimization [4]. Two cross-sectional studies from Norway found prevalence numbers of 80% among girls and 74% among boys in 2007, and 64% and 62%, respectively, in 2013 [5]. An American study found a lower prevalence at 29% and 20% for girls and boys respectively [6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rape, sexual coercion and sexual assault are considered some of the most severe forms of physical sexual harassment (Wane, 2009;Hill & Holly, 2011 psychologically traumatized and terrified besides eliciting lots of silence and denial (Mwiti, 1997;). In Britain, Canada, China, Israel, Norway and Germany SH is on an upward trajectory both in and out of secondary schools (Zeira et al, 2002;Canadian Press, 2008;Wei & Chen, 2011;Bendixen et al, 2018;Witt et al, 2018). In Canada, a survey of 1800 students carried out in 23 high schools showed that over 50% of girls were victims of unwanted sexual comments and gestures which affected their health, adjustment, worth and overall wellbeing in school (Canadian Press, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thirdly, in addition to individual characteristics, a body of literature has identified environmental characteristics that are related to sexual harassment. In addition to e-contexts [28], educational settings have been identified as a major arena for sexual harassment among young people [19, 29]. Some of the existing studies have found that certain aspects of the school context, including teacher maltreatment [22] and feeling disconnected from school [24], are linked to a higher prevalence of sexual harassment.…”
Section: Introductionmentioning
confidence: 99%